Investing in SRI Mutual Funds –An initiative to Sustainable development (General perspective of Delhi/NCR Investors) - Nagpal, Dr Ankita; Chadha, Mansi (The journal of contemporary issues in business and government, 2021)
Purpose: The article examines the awareness level of SRI mutual funds among Indian Investors and their perception regarding the return and risk associated with them. Design/Methodology/approach: To analyze the results one way empirical variance (ANOVA), chi-square analyses, descriptive analysis and factor analysis were used. Standardized questionnaire was supplied to 132 mutual funds Investor of Delhi/NCR. Findings: Indian financial specialists were benefit arranged and not morally situated. Age & qualification have little impact and revenue impacts the speculator type, female buy more SRI reserve then men. An overall viewpoint of SRI reserves, they offered not so much returns but rather more hazardous as contrast with Normal assets Research limitations/Implications: The study will be benefited for Asset Management Company to assist the awareness programs for investors and should launch SRI funds Originality/Value: Research unravels the relation of type of investor and demographic profile relate to socially responsible funds. A general view of Indian investors on SRI funds contributes to literature by trying to fill this gap.